(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1863)
This article discusses the use of plate-marks in the study of precious metals in Scotland. The author explains the purpose of each plate-mark from the Edinburgh Assay Office and the parliamentary act associated with it.